Characterization of procoagulant extracellular vesicles and platelet membrane disintegration in DMSO‐cryopreserved platelets. Issue 1 (4th May 2016) - Tegegn, Tseday Z.; De Paoli, Silvia H.; Orecna, Martina; Elhelu, Oumsalama K.; Woodle, Samuel A.; Tarandovskiy, Ivan D.; Ovanesov, Mikhail V.; Simak, Jan
Abstract : Background: Freezing is promising for extended platelet (PLT) storage for transfusion. 6% DMSO cryopreserved PLTs (CPPs) are currently in clinical development. CPPs contain significant amount of platelet membrane vesicles (PMVs). PLT‐membrane changes and PMV release in CPP are poorly understood, and haemostatic effects of CPP PMVs are not fully elucidated. This study aims to investigate PLT‐membrane alterations in CPPs and provide comprehensive characterization of CPP PMVs, and their contribution to procoagulant activity (PCA) of CPPs. Methods: CPPs and corresponding liquid‐stored PLTs (LSPs) were characterized by flow cytometry (FC), fluorescence polarization (FP), nanoparticle tracking analysis (NTA), electron microscopy (SEM, TEM), atomic force microscopy (AFM) and thrombin‐generation (TG) test. Results: SEM and TEM revealed disintegration and vesiculation of the PLT‐plasma membrane and loss of intracellular organization in 60% PLTs in CPPs. FP demonstrated that 6% DMSO alone and with freezing–thawing caused marked increase in PLT‐membrane fluidity. The FC counts of annexin V‐binding PMVs and CD41a + PMVs were 68‐ and 56‐folds higher, respectively, in CPPs than in LSPs. The AFM and NTA size distribution of PMVs in CPPs indicated a peak diameter of 100 nm, corresponding to exosome‐size vesicles. TG‐based PCA of CPPs was 2‐ and 9‐folds higher per PLT and per volume, respectively, compared to LSPs. Differential centrifugation showed that CPP supernatant contributed 26% to CPP TG‐PCA, mostly by the exosome‐size PMVs and their TG‐PCA was phosphatidylserine dependent. Conclusions: Major portion of CPPs does not show activation phenotype but exhibits grape‐like membrane disintegration with significant increase of membrane fluidity induced by 6% DMSO alone and further aggravated by freezing–thawing process. DMSO cryopreservation of PLTs is associated with the release of PMVs and marked increase of TG‐PCA, as compared to LSPs. Exosome‐size PMVs have significant contribution to PCA of CPPs.